Executive functioning and disinhibited eating in children and adolescents. Issue 6 (9th February 2020) - Kelly, Nichole R.; Jaramillo, Manuela; Ramirez, Sophie; Altman, Deborah R.; Rubin, Sarah G.; Yang, Shanna B.; Courville, Amber B.; Shank, Lisa M.; Byrne, Meghan E.; Lemay‐Russell, Sarah; Brady, Sheila M.; Broadney, Miranda M.; et al.
Summary: Background: Executive functioning (EF) difficulties may be associated with problems regulating eating behaviours. Few studies have evaluated this question in youth using diverse measures of EF or objective measures of energy intake. Methods: The current study used neuropsychological tasks and a laboratory test meal to evaluate the links between EF and youth's disinhibited eating patterns. Two‐hundred‐five nontreatment seeking youth ( M age = 13.1 ± 2.8 years; M BMI z = 0.6 ± 1.0; 33.2% overweight; 54.1% female) completed tasks measuring decision making, general and food‐specific behavioural disinhibition, willingness to delay gratification for food and money, cognitive flexibility, and working memory. Age (children vs adolescents) was examined as a moderator. All analyses adjusted for demographic factors, pubertal status, lean mass (kg), fat mass (%), height, general intellectual functioning, and depressive symptoms. Results: After adjusting for multiple comparisons, more general behavioural disinhibition was associated with greater total energy intake ( P = .02), and poorer cognitive flexibility was associated with more fat intake ( P = .03) across all ages. Poorer decision making in children ( P = .04), but not adolescents ( P = .24), was associated with greater fat intake. Food‐specific behavioural disinhibition, the ability to delay gratification for both food and monetary rewards, and working memory were not significantly associated with youth's disinhibited eating patterns during a single meal. Conclusions: Most domains of EF were not associated with youth's disinhibited eating. Significant associations may highlight the need to target specific cognitive processes, particularly behavioural disinhibition, decision making, and cognitive flexibility, in potential intervention strategies for children's disinhibited eating.